TUGAS DAN PELAKSANAAN WEWENANG DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM MENGADVOKASI ASPIRASI PETANI MELALUI PEMBENTUKAN PERATURAN DAERAH (PERDA) PERLINDUNGAN DAN PEMBERDAYAAN PETANI DI KABUPATEN BANJARNEGARA - Sri Rahayu Rahayu; Rakhmat Bowo Suharto (Jurnal Hukum Khaira Ummah, 2017)
Farmers in Banjarnegara Regency contribute to agricultural development and economic development, so it is very important to be given protection and empowerment through the making of local regulations made by the DPRD. Farming communities can participate in the formation of local regulations by giving their aspirations. However, there are obstacles in the implementation of duties and authority of DPRD in advocating the aspirations of farmers through the formation of local regulations.Keywords : Authority, Regional House of Representatives, Aspirations, and Re-gional Regulations